Ritual Nyera pada Mesin Kapal bagi Masyarakat Etnis Bajo di Desa Banu-Banua Jaya Kecamatan Kulisusu Kabupaten Buton Utara - Taufiq Said; La Ando La Ando; La Ode Ali Basri; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
This research aims to analyze the importance of the Nyera Ritual on Ship Engines for the Bajo Ethnic Community and the meaning of the Nyera ritual in the Bajo ethnic community in Banu-Banua Jaya Village, Kulisusu District, North Buton Regency. The research method for collecting data was carried out using observation, interviews and documentation techniques. Using Edward B Tylor's theoretical basis, the technique for determining informants uses the purposive technique. Data were analyzed using data collection techniques, data reduction, data presentation and drawing conclusions. The results of this research show that the importance of the Nyera ritual consists of 5 types: 1.) Purification, 2.) Protection/Safety, 3.) Preserve, 4.) Fortune, 5). Friendship. The meaning in the Nyera ritual has 3 types of meaning: 1.) The meaning of materials such as water, incense, chicken, 2.) The meaning of the Nyera Ritual process, namely reciting prayers on water, the meaning of bathing a chicken, the meaning of reciting prayers on a knife, the meaning of wiping chicken blood on each side of the machine. 3.) The meaning of the final stage of reading prayers on the machine so that all wishes are carried out. The Nyera Ritual can be fulfilled by the Almighty and the meaning of giving syndikka money so that the person giving the syndikka money has good fortune.